Four new species of Ursinia (Asteraceae, Anthemideae) from South Africa, with an updated key to the genus in Namaqualand - Magee, Anthony Richard; Boatwright, James S.; Mucina, Ladislav (Phytotaxa, 2014)
Recent field and herbarium studies of the southern African genus Ursinia (Anthemideae, Asteraceae) in Namaqualand, South Africa, have revealed greater morphological variability than currently accommodated and a high percentage of misidentified specimens. In an attempt to remedy this we herein describe four new species (Ursinia arida, U. glandulosa, U. kamiesbergensis and U. laciniata) and provide a key to the species in the region, together with illustrations of their involucral bracts and paleae. The species can be distinguished by a combination of their life history, vestiture, presence or absence of appendages on the paleae, and shape of the involucral bracts and their scarious apices.